Development of clinical pathway for non-surgical management of chronic periodontitis - Kamil W.; Hian O.Y.; Mohd-Said S.; Zainuddin S.L.A.; Ramli H.; Noor E.; Ayob R.; Aziz A.F.A.; Ismail A.; Sulong S.; Mohd-Dom T.N. (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus